2006
DOI: 10.1002/cbdv.200690080
|View full text |Cite
|
Sign up to set email alerts
|

New Bisabolane Sesquiterpenes and Coumarin from Leontopodium longifolium

Abstract: From the roots of Leontopotium longifolium, three new bisabolane sesquiterpenes, rel-(1S,4R,5S,6R)-4,5-diacetoxy-6-[(R)-1,5-dimethylhexa-3,5-dienyl]-3-methylcyclohex-2-enyl (Z)-2-methylbut-2-enoate (1), rel-(1S,4R,5S,6R)-4,5-diacetoxy-6-[(R)-5-hydroxy-1,5-dimethylhex-3-enyl]-3-methylcyclohex-2-enyl (Z)-2-methylbut-2-enoate (2), rel-(1R,2S,4R,5S)-4-acetoxy-2-[(R)-5-hydroxy-1,5-dimethylhex-3-enyl]-5-methylcyclohexyl (Z)-2-methylbut-2-enoate (3), and a new coumarin, 2,3-dihydro-5-hydroxy-2-(1-methylethenyl)-7H-py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Unfortunately, m / z values of 477.1 and 459.0 could not be identified. Comparison with literature data suggested that the m / z value of 459 corresponds to a bisabolane derivative isolated from L. longifolium (= L. souliei ; Li et al, 2006). …”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Unfortunately, m / z values of 477.1 and 459.0 could not be identified. Comparison with literature data suggested that the m / z value of 459 corresponds to a bisabolane derivative isolated from L. longifolium (= L. souliei ; Li et al, 2006). …”
Section: Resultsmentioning
confidence: 78%
“…Despite these results, nearly nothing is known about bioactive compounds in other Leontopodium species. Until now, only a few phytochemical and pharmacological investigations have been conducted on these species (e.g., Leontopodium longifolium Ling: Li et al, 2006; Leontopodium leontopodioides Beauverd: Li et al, 1994; Leontopodium andersonii C.B. Clarke: Schwaiger et al, 2010; Leontopodium nanum Hand.-Mazz.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have affirmed that Leontopodium longifolium has anti-inflammation and cough abilities [36]. Persuasive evidences have substantially reported pivotal function of Aβ induced the generation of free radicals which expedite oxidative stress that contributes a lot to process of AD [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…81 Another three new sesquiterpenes 90-92 have been isolated from the roots of Leontopodium longifolium. 82, 83 Baccharisketone 93 is another new bisabolane derivative, which has been obtained from the leaves of Baccharis dracunculifolia. 84 The active principle of an extract from the roots of Ostericum koreanum 85 which affects adults of the Dermatophagoides genus, has been identified as the known sesquiterpene bisabolangelone 94.…”
Section: Bicyclofarnesanementioning
confidence: 99%